Effects of Vestibular Rehabilitation in the Management of a Vestibular Migraine: A Review - Alghadir, Ahmad H.; Anwer, Shahnawaz (Frontiers in Neurology, 2018)
Vestibular rehabilitation (VR) has been shown to be effective for many vestibular disorders. This review focuses on the current evidence on the effects of physical therapy in the management of vestibular symptoms in individuals with a vestibular migraine (VM). The individuals with a history of a migraine tend to have a high incidence of vestibular symptoms with some or all of their headaches. A total of six included studies investigated the effects of VR in the management of VM. The critical review form for quantitative studies was used to appraise quality assessment and risk of bias in the selected studies. Previous studies validated the use of VR in the treatment of vestibular symptoms for individuals with a vestibular migraine to include improved headache and migraine-related disability in patients with a vestibular migraine. From the current evidence, it is difficult to provide conclusive evidence regarding the efficacy of VR to minimize vestibular symptoms in patients with VM. Therefore, more randomized controlled studies are required to make firm evidence on the effect of VR in reducing vestibular symptoms in patients with VM. The future prospective, blinded, randomized controlled studies may help to isolate possible therapeutic effects of VR and other general effects.